Dampak Masuknya Bahasa Asing Terhadap Eksistensi Bahasa Indonesia di Era Globalisasi - Situmorang, Adventina; Br.Sitepu, Berliana Putri Ananty; Pulungan, Garda Ali; Simatupang, Ihsan Mubarok; Alamsyah, Rahmad Darmawan; Pulungan, Hendra Kurnia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Globalization in the 21st century has significantly impacted language use in Indonesia, particularly through the dominance of English as the global lingua franca. This phenomenon provides broader access to knowledge and international communication but simultaneously poses serious challenges to the status and function of the Indonesian language. This study employs a qualitative approach based on literature review, using a sociolinguistic framework and critical discourse analysis. The findings reveal the emergence of over 1,100 new loanwords, a high prevalence of code-mixing among younger generations—reaching up to 80%—and a noticeable shift in language attitudes among university students and urban communities who increasingly favor foreign terms. These findings suggest that the influx of foreign languages not only enriches the lexicon but also potentially undermines the role of Indonesian as a symbol of national identity and a medium of academic discourse. Therefore, firm language policies, the development of relevant and adaptive terminology, and the cultivation of collective awareness are essential to ensure the sustainability and strengthening of the Indonesian language as both a unifying language and a language of knowledge in the era of globalization.